A rare triad of diabetic ketoacidosis, hypertriglyceridemia and acute pancreatitis: a case report - Kumar, Manoj; V., Vijayavarman; Kumar, Pawan; Das, Arindam (International Journal of Research in Medical Sciences, 2019)
Diabetic ketoacidosis (DKA), Acute Pancreatitis and Hypertriglyceridemia are an unusual and infrequent presentation of Diabetes. Hypertriglyceridemia leading to acute pancreatitis is most commonly encountered in poorly controlled Diabetics. In this case report we have described a young Type 1 Diabetic female presenting with Diabetic Ketoacidosis and hypertriglyceridemia induced Pancreatitis (HTIP). The proposed mechanism is triglyceride excess is hydrolyzed by pancreatic lipase resulting in the formation of excess free fatty acids. Excess free fatty acids cause acinar cell injury and capillary leakage in pancreatic vascular beds. Hyperlipasemia frequently occurs in DKA without an underlying acute pancreatitis. Half of the patients with HTIP have falsely low or normal serum Amylase. Imaging is required to confirm the diagnosis of pancreatitis. So, high degree of suspicion is required to diagnose this unusual presentation of diabetes.